العلاقة بين الأسرة والمدرسة في ضوء التشريع المدرسي الجزائري - مسعي محمد, أحمد; غربي, خالد (جامعة الوادي - University of Eloued, 2023)
لا تستطيع المدرسة أداء رسالتها التعليمية والتربوية على أكمل وجه ما لم يتحقق التعاون فيما بينها وبين الأسرة حيث أن لكل منها مسؤولية عظيمة في تربية النشئ. ومن منطلق هذه المسؤولية يتطلب تعميق العلاقة بينهما، حيث حظى هذا المبدأ التربوي أي موضوع أي العلاقة بين الأسرة والمدرسة باهتمام كبير من جانب العلماء التربويين وعلماء الاجتماع والنفس، وللتحقيق ذلك فتح نظامنا التربوي في الجزائر نافذة للارتقاء بهذه العلاقة. ومنه جاءت هذه الورقة البحثية لتقف وتستعرض أهم النصوص التشريعية المدرسية لنظام التربوي الجزائري، التي تناولت هذه العلاقة وسبل توثيقها.Abstract: The school cannot perform its educational mission to the fullest unless there is cooperation between it and family , since each has a great responsibility in raising the young . This sense ,it is necessary to deepen the relationship between them , where this educational principle has been the subject of the relationship between the family and the school with the great attention of educational scientists and sociologists and psychologists , and to achieve this the Algerian educational system has opened a window to improve this relationship. This paper aims at the most important legislative texts of the educational system that dealt with this relationship and ways of documenting it .
مقال
Keywords: العلاقة - الأسرة -المدرسة -التشريع المدرسي; relationship ; family ; the school ; school legislation